Government Intervention in Agriculture Market Management - Poudel, Shuvam; Karki, Rojan; Sharma, Subash (Nepalese Journal of Agricultural Sciences, 2025)
This review critically examines government intervention in agriculture through policies and bilateral agreements, focusing on mechanisms such as the Minimum Support Price (MSP), input subsidies, crop insurance, extension services, and market regulations. A review of existing literature reveals that although these interventions aim to support farmers and stabilize the agricultural economy, their implementation is often flawed. Key findings highlight systemic gaps: MSP programs face delays and insufficient procurement; input subsidies suffer from targeting inefficiencies and elite capture; crop insurance adoption remains limited due to accessibility barriers; and the federalization of extension services has led to institutional fragmentation. The study has deduced that, despite considerable effort by the government, its efficacy and accessibility to common farmers remain far-fetched, and it is confronted with several technical and infrastructure shortcomings.